Reporting Solution for Order Management - Darko Golec (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
Order Management provides order orchestration through a centralised inventory, order promising and fulfillment hub to support omni-channel fulfillment. Reporting solution on top of Order Management application consists of multiple business reports that provide reliable information to the business people. The system enables to make better decisions how to promise and fulfil customer orders, resulting in improved profitability and customer satisfaction. In this paper, written as use case, some of the key points of the implementation are presented, deployed for a global durable goods company.
Keywords: G31; L81; M11; 330; Reporting; Business Intelligence; Data Warehouse; Order Management